2018
DOI: 10.1111/eth.12805
|View full text |Cite
|
Sign up to set email alerts
|

Quiet violence: Savannah Sparrows respond to playback‐simulated rivals using low‐amplitude songs as aggressive signals

Abstract: When animals compete over resources such as breeding territories, they often use signals to communicate their aggressive intentions. By studying which signals are associated with aggressive interactions, we gain a deeper appreciation of animal behaviour. We studied aggressive signalling in male Savannah Sparrows, Passerculus sandwichensis, focusing on signals that precede physical attack against territorial intruders. We simulated intruders using song playback and taxidermic models, and we determined which beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…We found that playback of male soft song provoked a significantly stronger aggressive intent response than broadcast songs in the Plain Laughingthrush, perhaps because the responder perceives the intruder to be closer, as the signal was played at a much lower amplitude. This finding is consistent with other studies of other passerines including Eurasian Blackbird Turdus merula (Dabelsteen & Pedersen 1990), Brownish-flanked Bush Warbler Horornis fortipes (Xia et al 2013), Savannah Sparrow Passerculus sandwichensis (Moran et al 2018), Dark-eyed Junco Junco hyemalis (Reichard et al 2011) and Song Sparrow Melospiza melodia (Anderson et al 2012, Templeton et al 2012. However, in the Ortolan Bunting Emberiza hortulana, soft song is used by males in an aggressive context, although it does not appear to represent a true aggressive signal (Jakubowska & Osiejuk 2018).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that playback of male soft song provoked a significantly stronger aggressive intent response than broadcast songs in the Plain Laughingthrush, perhaps because the responder perceives the intruder to be closer, as the signal was played at a much lower amplitude. This finding is consistent with other studies of other passerines including Eurasian Blackbird Turdus merula (Dabelsteen & Pedersen 1990), Brownish-flanked Bush Warbler Horornis fortipes (Xia et al 2013), Savannah Sparrow Passerculus sandwichensis (Moran et al 2018), Dark-eyed Junco Junco hyemalis (Reichard et al 2011) and Song Sparrow Melospiza melodia (Anderson et al 2012, Templeton et al 2012. However, in the Ortolan Bunting Emberiza hortulana, soft song is used by males in an aggressive context, although it does not appear to represent a true aggressive signal (Jakubowska & Osiejuk 2018).…”
Section: Discussionsupporting
confidence: 91%
“…2013), Savannah Sparrow Passerculus sandwichensis (Moran et al . 2018), Dark‐eyed Junco Junco hyemalis (Reichard et al . 2011) and Song Sparrow Melospiza melodia (Anderson et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stimuli were presented in a randomized order, and each stimulus set was used at least twice. The response duration and behaviours of males (crouching with head feathers flattened close to the skull, aggressive displays 48 and vocalizations 90 ) were noted. We used duration, measured as time from the end of the stimulus presentation until the male ceased responding (defined as moving 20 m or more away from the speaker, or singing a full and loud song, or engaging in feeding or preening behaviour), as our primary measure of male response 55 .…”
Section: Methodsmentioning
confidence: 99%